Hidup dan Pelayanan Yesus sebagai Landasan Pendidikan Kristen - Sarah Wassar; Juanda Yulianus; Kezia Verena; Lia Lesty S; Lidiawati Lidiawati (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
Christian education lessons are held at home, church and school. The importance of Christian education is seen in the life and ministry of Jesus Christ while He was on earth. The Bible as the basis of Christian Education which leads believers to know the person, life and ministry of Jesus as a reality for the foundation of Christian education. So that Christians can carry out the task of the Lord Jesus' great commission, (Matthew 28: 19-20), namely to make disciples of all nations and teach them to do everything that the Lord Jesus commands. This research was conducted using a qualitative method, namely literature or literature in the form of theological analysis as a basis for teaching biblical Christian education.